17=3(23-b)+2(b-2)

Simple and best practice solution for 17=3(23-b)+2(b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17=3(23-b)+2(b-2) equation:


Simplifying
17 = 3(23 + -1b) + 2(b + -2)
17 = (23 * 3 + -1b * 3) + 2(b + -2)
17 = (69 + -3b) + 2(b + -2)

Reorder the terms:
17 = 69 + -3b + 2(-2 + b)
17 = 69 + -3b + (-2 * 2 + b * 2)
17 = 69 + -3b + (-4 + 2b)

Reorder the terms:
17 = 69 + -4 + -3b + 2b

Combine like terms: 69 + -4 = 65
17 = 65 + -3b + 2b

Combine like terms: -3b + 2b = -1b
17 = 65 + -1b

Solving
17 = 65 + -1b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add 'b' to each side of the equation.
17 + b = 65 + -1b + b

Combine like terms: -1b + b = 0
17 + b = 65 + 0
17 + b = 65

Add '-17' to each side of the equation.
17 + -17 + b = 65 + -17

Combine like terms: 17 + -17 = 0
0 + b = 65 + -17
b = 65 + -17

Combine like terms: 65 + -17 = 48
b = 48

Simplifying
b = 48

See similar equations:

| 4x+7=108 | | x(3x^2+6x+-1)+4x= | | x(3x^2+6x+-1)+4x=0 | | F(x)=-x^2-80x-1800 | | 8x+14y= | | x^3=1500 | | 28z^2+28z+15= | | x+3/6=x+1/4 | | X^2+10+13-4=0 | | 50+2x-4=100 | | 59=35-4(x-2) | | 5x-8x+15=2x+30 | | 8x-(6x+3)=4x-21 | | (3w+7)(1-w)=0 | | 5=x+25 | | (3w+7)(1+w)=0 | | 4x-5=28-2x | | 1.6y+y=5421 | | f(x)=9x+9x^2 | | 12-2x=2x | | 5n-15=2n+12 | | 4x-5=29-2x | | (-6)x+1=216 | | (.6)x+1=216 | | (4y-5)(3-y)=0 | | (4w-9)(7-w)=0 | | Lny=2 | | Gf(x)=log(4x-1) | | Lgy=2.075 | | ln(19)=ln(2)+ln(x+6) | | 2x^2+y^2=9 | | 4x^2-16x-6=0 |

Equations solver categories